Customer Loyalty Patterns in Traditional Retail Pricing and Service Quality: Polanya Loyalitas Pelanggan dalam Penetapan Harga dan Kualitas Layanan di Ritel Tradisional - Yusril Nur Alfiansyah; Rizky Eka Febriansah; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Customer loyalty is a strategic factor for business sustainability, particularly in retail sectors facing intense competition. Specific Background Traditional retail businesses such as UD. Haji Nur rely heavily on pricing strategies and service quality to retain customers in local markets. Knowledge Gap Previous studies show inconsistent findings regarding the mediating role of customer satisfaction in the relationship between price, service quality, and customer loyalty. Aims This study examines customer loyalty in relation to price and service quality, with customer satisfaction as an intervening variable at UD. Haji Nur. Results Using a quantitative approach and SEM-PLS analysis on data from 100 respondents, the findings indicate that price and service quality are positively associated with customer loyalty and customer satisfaction, while customer satisfaction also demonstrates a significant association with loyalty and mediates both relationships. Novelty This research provides empirical evidence from a long-established traditional retail agent context, highlighting customer satisfaction as a central mechanism. Implications The findings offer practical insights for traditional retailers in managing pricing and service strategies to sustain customer loyalty and support long-term business continuity. Keywords: Price, Service Quality, Customer Satisfaction, Customer Loyalty, Traditional Retail Key Findings Highlights Pricing and service dimensions are consistently associated with repeat purchasing behavior. Satisfaction functions as a central mediating mechanism in customer retention. Traditional retail agents demonstrate loyalty dynamics similar to modern retail contexts.